Monitoring Measurable/Minimal Residual Disease in Acute Myeloid Leukemia: Multiparametric Flow Cytometry-Based Approach - Tembhare, Prashant Ramesh (Indian Journal of Medical and Paediatric Oncology, 2023)
Measurable/minimal residual disease (MRD) status is the most relevant predictor of clinical outcome in hematolymphoid neoplasms, including acute myeloid leukemia (AML). In contrast to acute lymphoblastic leukemia, multiple myeloma, or chronic lymphocytic leukemia, etc., AML is a widely heterogeneous neoplasm with poor clinical outcomes. Multicolor flow cytometry (MFC) is a powerful technology with high sensitivity, rapid results, cost-effectiveness, and easy availability. It is routinely used for diagnosing and MRD monitoring in many hematological neoplasms. However, MFC-based MRD monitoring in AML is complex and challenging. It requires a refined approach, a wide panel of markers, and adequate training and experience. This review focuses on the panel design, processing details, template design, analysis approach, and recent updates in MFC-based MRD monitoring in AML. It further describes the normal distribution and maturation patterns of various sublineages among hematological progenitors and their utility in studying AML MRD.
Keywords: flow cytometry; minimal residual disease; acute myeloid leukemia